MRI Features of Free Liquid Silicone in the Transgender Female Breast. Issue 3 (19th April 2021) - Sonnenblick, Emily B; Chaudhry, Shivani; Lee, Karen A; Jaffer, Shabnam; Fang, Frank; Ting, Jess; Margolies, Laurie R
Abstract: Objective: To define MRI features of free liquid silicone injection (FLSI) of the breast in transgender women considering surgical management. Methods: This study was IRB–approved. MRI images from transgender women with FLSI imaged between 2009 and 2019 were reviewed. Presence and location of fibrotic masses (FMs) in the breast(s) and pectoralis muscle and patterns of granulomas were correlated with clinicopathologic findings. Background enhancement was quantified. Comparisons were performed using two-tailed Fisher exact and Student's t test. Results: Of 21 transgender women with FLSI (mean age 46.8 years), 13/21 (61.9%) had a dominant FM measuring over 4 cm; these were limited to breast and pectoralis in 6/21 (28.6%), breast in 9/21 (42.9%), and pectoralis only in 2/21 (9.5%). Four of 21 patients (19.0%) had no FMs, and 4/21 (19.0%) had masses under 4 cm. Mean size of the dominant FM was 7.4 cm (range 4–12 cm). FMs were enhancing in 5/13 (38.5%) and contained T2 high signal granulomas in 8/13 (61.5%). While 18/21 (85.8%) of cases showed mild to moderate overall background enhancement, the majority 7/13 (61.5%) of dominant FM were non-enhancing. About half of cases (11/21, 52.4%) had diffuse foci, and half (10/21, 47.6%) had diffuse foci and masses throughout the breast and pectoralis muscle. These foci and masses displayed T2 high signal in 13/21 (61.9%). There were no occult carcinomas observed. Conclusion: MRI performed on symptomatic FLSI patients considering surgical treatment is helpful in assessing the extent of silicone infiltration and fibrotic reaction of the breast and pectoralis muscle. Graphical Abstract: